PENGARUH KEPUTUSAN PENDANAAN DAN KEBIJAKAN DEVIDEN YANG DIMEDIASI RESIKO KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA(BEI) PRIODE 2008-2012 - Ayuni '; Yulia Efni; Haryetti ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The aim of the research is to test the direct and indirect effect of financing decision and dividend policy in mediated by risk toward firm value the company manufactures a variety of industrial sectors companies listed in Indonesia Stock Exchange (IDX) period 2008-2012. The population of the research is 54 company and the variety of industry sectors into a sample of 21 companies by N of data as much as 105. The sampling method used is based purposive sampling. Data analysis using descriptive analysis and path analysis. By path analysis, some important findings are obtained that financing decisions no significant influence directly toward firm value, dividend policy did not significantly influence directy toward firm value, Financing decisions no significant influence directly toward Financial risk. dividend policy did not significantly influnce directly toward financial risk, while the financial risk significatly effects on firm value. This means indirectly the financial risk is not able to mediate the relationship between financing decisions toward firm value. This means indirectly the financial risk is not able to mediated the relationship between the dividend policy firm value.Keywords: Financing Decision,Dividend Policy, Financial Risk, the firm Value